Gel Polymer Electrolytes Design for Na‐Ion Batteries. Issue 11 (13th October 2022) - Pan, Jun; Wang, Nana; Fan, Hong Jin
Abstract: Na‐ion battery has the potential to be one of the best types of next‐generation energy storage devices by virtue of their cost and sustainability advantages. With the demand for high safety, the replacement of traditional organic electrolytes with polymer electrolytes can avoid electrolyte leakage and thermal instability. Polymer electrolytes, however, suffer from low ionic conductivity and large interfacial impedance. Gel polymer electrolytes (GPEs) represent an excellent balance that combines the advantages of high ionic conductivity, low interfacial impedance, high thermal stability, and flexibility. This short review summarizes the recent progress on gel polymer Na‐ion batteries, focusing on different preparation approaches and the resultant physical and electrochemical properties. Reasons for the differences in ionic conductivity, mechanical properties, interfacial properties, and thermal stability are discussed at the molecular level. This Review may offer a deep understanding of sodium‐ion GPEs and may guide the design of intermolecular interactions for high‐performance gel polymer Na‐ion batteries. Abstract : This review highlights the recent advance in sodium ion gel polymer electrolytes, covering the typical synthesis approaches, different physical/electrochemical properties, and their relationship with the various synthesis methods that is analyzed from the molecular level.